INCENTIVIZING OPENNESS: THE INFLUENCE OF MANAGERIAL COMPENSATION ON VOLUNTARY DISCLOSURE - Gharbi, Imen (PEOPLE: International Journal of Social Sciences, 2024)
This paper analyzes the relationship between voluntary disclosure and managerial compensation in the French context. Our analysis is based on a sample of non-financial French firms listed on the SBF120. By using a score of voluntary disclosure, the results show a significant and positive relationship between managerial compensation and the score of voluntary disclosure. The findings of this study also indicate that there is a relationship between voluntary disclosure and firm’s characteristics. Our results provide a better understanding of voluntary disclosure practices and draw more attention of regulatory authorities to the importance of managerial compensation to improve transparency and voluntary disclosure.